Інтенсифікація пінних апаратів - Моїсєєв, Віктор Федорович; Манойло, Євгенія Володимирівна; Глушко, Г. Д. (ВІЦ "Місто", 2016)
The ammonia-soda method makes it possible to provide continuous production. The main disadvantage of this method are ammonia wastes are discarded in the socalled “white sea”. Ammonia is not included in the final product – soda, and after regeneration of ammonium chloride is returned again to ammonization of brine. The main flow of ammonia fed to the ammonization station from the Department of distillation. Some ammonia is sent to the ammonization station of gases from the Department of carbonation and air is sucked from drum vacuum filters.
Keywords: пінні апарати; стабілізатори піни; переробка конденсатів; газ; миноподібні насадки